§ 1.

       2. f(x).

 

2.01. f(x) = 2x2 + 3x 1;

2.02. f(x) = 2x3 + 3x2 2 + 1;

2.03. f(x) = 2x4 x3 3;

2.04. f(x) = x4 2x3 3 1;

2.05. f(x) = 2x6 3x4 + 7;

2.06. f(x) = 3x3 2x2 + 6;

2.07. f(x) = 5x2 3x + 2;

2.08. f(x) = 7x4 2x3 3 2;

2.09. f(x) = 8x6 3x4 5 3;

2.10. f(x) = 3x4 2x2 + 6;

2.11. f(x) = 3x3 2x2 + 1;

2.12. f(x) = 2x4 x2 + 3 + 1;

2.13. f(x) = x4 2x + 1;

2.14. f(x) = x4 3x3 2 1;

2.15. f(x) = x3 + 3x2 4;

2.16. f(x) = 2x5 3x4 + 6 2;

2.17. f(x) = 3x4 2x3 8;

2.18. f(x) = x6 2x4 3;

2.19. f(x) = 4x6 x3 2 + 3;

2.20. f(x) = 2x3 4x2 2 3;

2.21. f(x) = x6 2x3 3;

2.22. f(x) = 4x3 2x2 1;

2.23. f(x) = x4 2x2 + 3;

2.24. f(x) = 2x2 3x  + 6;

2.25. f(x) = 6x3 2x2 + ;

2.26. f(x) = 3x4 x2 + 3 2;

2.27. f(x) = 5x4 x3 + 2 + 5;

2.28. f(x) = 2x6 3x3 + 2 4;

2.29. f(x) = 4x4 x3 + 3;

2.30. f(x) = 4 2x + x2 ;

2.31. f(x) = 7 2x 3x2 3;

2.32. f(x) = 2 3x + 5x4;

2.33. f(x) = 4 + 8x 6x3 ;

2.34. f(x) = 3 x 2x2 + 2;

2.35. f(x) = 3x8 2x2 3 + 4;

2.36. f(x) = 4x5 x3 + 2 3.

 

\..\

                              Copyright © 2008-2009 ..   . .